THE EFFECT OF INTERNAL CONTROL ON THE RECEIVABLES MANAGEMENT - Indra Patuan; Ancella Anitawati Hermawan (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
Problems related to the balance of bad debts in a company or government entity that conducts operational transaction activities are still a strategic issue. Many entities that have bad receivables balances eventually experience liquidity difficulties due to unbillability of bad receivables balances. This research was conducted at BPH Migas. As a government agency that manages non-tax state revenues through the receipt of contributions from business entities, issues related to the settlement of bad debts are still a big theme that continues to be a concern. Although the procedure for settling bad debts refers to policies regulated by the Ministry of Finance, the fact is that the value of bad receivables balances presented in the 2021 and 2022 financial statements has increased consecutively. The purpose of this study is to determine the effect of internal control on the administration of receivables, especially in order to reduce the potential for bad debts. The data analysis used in this study is qualitative descriptive through Internal Control System testing analysis. The respondents involved are those in charge of activities as well as related stakeholders such as business entities. The results of this study reveal that internal control at BPH Migas in the administration of receivables has not been fully adequate and has an influence on the unresolved balance of bad debts.